TRADISI MASYARAKAT DALAM MELAKSANAKAN SHALAT TARAWIH DI RUMAH SIEMPU NEGERI DESA KEBUNDURIAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR RIAU - Amanan Amanan (Ensiklopedia of Journal, 2019)
The tradition of tarawih prayer in Islam is carried out uniquely by the people of Kebundurian. The implementation is synchronized with the village custom, which upholds the traditional leader known as Siompu, the headman, and formal government. All problems faced by the community can be solved within the soko (tribe). All issues are recorded in as much detail as possible at the Tarawih prayer and it is known which tribes have problems. Checking the problems in each tribe aims to solve the problem properly, so that it can improve the relationship of all members of the community. If there are still problems in the soko (tribe) or so-called "cross crossover" that cannot be resolved, then each chief in Kebundurian conveyed to the traditional forum which consisted of Datuk Penghulu, dubalang, malin soko, imam, khatib, bilal, village chief community leader. After the submission of each chief was completed, the forum took action. Keywords: Society, Tarawih Prayers, Siempu Negeri, Kebundarian Village.